Piscean Diversity of Simen River, Dhemaji, Assam, North East India - Faruk Ahmed; Saimoun Ken Manhai; Dr. Pabitra Sarmah, (Indian Journal of Advanced Zoology (IJAZ), 2025)
The availability of ichthyofaunal diversity in a riverine ecosystem is a good indicator of river health. A good ichthyofaunal diversity of a riverine ecosystem represents a balanced ecosystem of the river. Taking this ecological conception into consideration, the ichthyofaunal diversity of the Simen River is studied during the present investigation. The Simen River in the district of Dhemaji, Assam, is a Himalayan tributary of the Brahmaputra River system, which flows through Arunachal Pradesh and Assam. Samples were collected fortnightly early in the morning from September 2022 to August 2023. Different types of nets and gears were found to be used by the fishermen. Collected fish were preserved in 5% formalin on the spot and brought to the laboratory for identification. The collected fish were identified up to the species level. A total of 43 species of fish belonging to 33 genera and 21 families were identified from the river during the study period. The family Cyprinidae was found to be the most dominant among the fish families.